COMPLETENESS, CONVERGENT MORPHOLOGY AND POSITIVE NARRATIVES: AN INTRIGUING SNAKE SKULL FROM THE MIDDLE-LATE EOCENE OF ARGENTINA (Ameghiniana, 2026)
We describe a partial snake neurocranium recovered from Eocene levels of the Geste Formation (Catamarca, Argentina). Preservedbones are fused, and the otic capsules are relatively enormous with a large stapedial footplate closing the fenestra ovalis. μCT imagery allows the recognition of a fenestra pseudorotunda that communicates the vestibular cavity with the juxstastapedial recess, and the occipital condyle is rounded (i.e., fovea dentis absent). This unusual combination of features known elsewhere only in uropeltid snakes, a group of Indian and Sri Lankan basal alethinophidians related with other Indomalayan snakes that together comprise the clade Uropeltoidea. A thorough anatomical analysis of skull of cryptozoic and surface-dwelling miniaturized colubroideans demonstrates that a fenestra pseudorotunda and the fusion of neurocranial bones are also present in other ophidian clades, thus questioning the diagnostic value of these features. A combined phylogenetic analysis (morphology plus DNA) places this fossil specimen as an uropeltoid. If new and more complete specimens confirm this result, Indomalayan uropeltoid snakes would represent a biogeographic puzzle that implies its probable origin in a Gondwanan terrain and a dispersion to peninsular India, Sri Lanka and South East Asia between the Late Cretaceous to the Paleogene. However, the fragmentary nature of the specimen, in conjuction with the pervasive morphological convergence observed among burrowing and surface-dwelling miniaturised snakes, suggests that caution is warranted. Pressure upon scientists to boost their publication output in high-ranked journals can potentially lead to the elaboration of attractive, positive narratives about complex evolutionary and paleobiogeographic scenarios, even when based on fragmentary specimens. Due to the often limited informativeness of fragmentary specimens, such evolutionary hypotheses are often weakly supported and thus have the potential to impede, rather than facilitate, the advancement of knowledge concerning ophidian evolution.